Em nome da civilização: guerra social, colonização, extermínios e política moderna - Marestoni, Matheus Dias de Lemos (2024)
This study is composed of three parts hat address how, in the name of Western civilization, colonial universals have been configured over the centuries through a permanent war between standardizing forms (which reshape and change) against different ways of life. The first movement deals with the planetary expansion of the subject from European colonial enterprises to the so-called New World initiated between the 15th and 16th centuries, focusing on exterminations and discursive production about the peoples who lived there, considered as savages. In this thesis, it is understood that such formulations underpinned the theory of sovereignty and contractualism of the 17th and 18th centuries. Hence, modern politics appears as a continuity of colonial war. The second part shows the emergence of the citizen as a new standardizing universal from the French Revolution, influenced by Enlightenment rationality, with special emphasis on categories such as Human and Reason. These notions, as well as the discussions surrounding them, were key elements in establishing a type of dividing line between the figure of the civilized and other individuals who escape this form, understood as uncivilized and primitive. Those treated as inferior for not fitting into the model of the rational European citizen were – and to some extent still are – understood as someone subjected to subordination and, ultimately, extermination, in what we consider here as an extension of colonial war. Finally, as the third and last part, we return to the contemporary context of neoliberal rationality to situate the emergence of the latest universal of the Western civilizational project: the democratic citizen, moderate, civilized, all too civilized